Variations in antibiotic resistance and plasmid content in Escherichia coli isolates from the normal intestinal flora and clinical sources - Younus et al. (Rwanda Medical Journal)
INTRODUCTION: Escherichia coli is one of the most important bacteria in the normal intestinal flora. The current study aimed to investigate their possession of antibiotic resistance and plasmids compared with their clinical isolates to determine the extent of their risk and health importance.